Creation of an Early Victorian Suburb in Montreal - Hanna, David (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
Montreal's "terrace townscape" emerged in the 1850s and 1860s and has since disappeared. It represented a conjuncture of forces peculiar to Montreal among British North American cities. The terrace — the uniting of a homogeneous group of attached houses behind a single monumental facade — concentrated on a plateau, between the older city to the south and the high-prestige homes on the slope to the north. Such housing flowed, in one sense, from the speculative development of wealthy landowners. The developnent was driven by the growth of the city and the concurrent housing boom of the 1850s and 1860s, coupled with the desire of the better classes to move from the noisome, dangerous and constricted older areas. Improvements in the urban infra-structure, especially the construction of water-works, made new development on higher lands feasible. The "terrace" form or fashion also derived from an architecturally and socially acceptable formula, rooted in British precedents, especially those of prestigious London. It was, finally, a form or fashion that was "indubitably linked with a strong upper middle class sector of the population" found only in administrative and commercial cities, and in British North Anerica found only in sufficient strength in Montreal.